The Impact of Basic Macroeconomic Variables and Market Risks on Borsa Istanbul Indices: A Comparative Sectoral Analysis - Erdem Bağci; Musa Bayir (Review of Business and Economics Studies, 2025)
The aim of this study is to empirically investigate the impact of various macroeconomic variables on the Borsa Istanbul Benchmark and Sectoral Indices. The impetus for this inquiry stems from the significant fluctuations in macroeconomic variables within the Turkish economy, particularly during the early 2020s. We utilized the Autoregressive Distributed Lag (ARDL) methodology to examine the dataset covering the period from 2013 to 2024. The results indicate that, in the long term, the Borsa İstanbul (BIST) general indices are negatively affected by interest rates and credit default swaps (CDS) premiums, while exchange rates positively influence them. Notably, there is no discernible impact from US interest rates, inflation, or gold prices; however, the influence of the volatility index (VIX) is observed to be significant only in the short term. When examining sectoral effects, the negative impacts of interest rates and CDS premiums, as well as the positive influence of exchange rates, are consistent across sectors, with particularly pronounced effects in the banking and real estate sectors. Conversely, the effects of US interest rates, inflation, gold prices, and the VIX index mirror those observed in the general indices. An interesting finding is that while the VIX fear index only negatively affects bank and construction company stocks in the long term, companies in almost all sectors are affected by global risks in the short term. The key conclusion of the research is that exchange rates and domestic risk indicators — such as interest rates and CDS premiums — are the most influential long-term drivers of Turkey’s stock market and sectoral performance, whereas global factors like US monetary policy and the VIX primarily affect short-term dynamics and investor sentiment.